2011
DOI: 10.1159/000335820
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced Obesity Up-regulates the Abundance of GPR43 and GPR120 in a Tissue Specific Manner

Abstract: Background/Aims: GPR43 and GPR120 have recently been deorphanised as receptors for fatty acids. Fatty acids mediate a variety of metabolic processes in the body, however, the effect these receptors have on metabolism is not fully understood. Here, we characterise the effect of diet-induced obesity on the expression of GPR43 and GPR120 in tissues important in maintaining metabolic health. Methods: Six-week old male Sprague Dawley rats were fed either a high fat diet (HFD; 22% fat) or control diet (5% fat; n = 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 77 publications
6
53
0
Order By: Relevance
“…SCFAs are thought to contribute to energy harvest and de novo lipogenesis (55), and fermentation in the proximal large bowel is a sign of small intestinal bacterial overgrowth, which leads to increased gut permeability and bacterial endotoxin reaching the liver (26). In addition, it recently has been shown that a 12-wk HFD resulted in increased FFAR2 (SCFA receptor) expression in liver and skeletal muscle (12). Here, we report that acute HFD feeding elicited no appreciable differences in hepatic mRNA expression of IL-1␤, TLR-4, or FFAR2 in HCR or LCR rats, suggesting that 3 days of HFD did not induce a hepatic inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs are thought to contribute to energy harvest and de novo lipogenesis (55), and fermentation in the proximal large bowel is a sign of small intestinal bacterial overgrowth, which leads to increased gut permeability and bacterial endotoxin reaching the liver (26). In addition, it recently has been shown that a 12-wk HFD resulted in increased FFAR2 (SCFA receptor) expression in liver and skeletal muscle (12). Here, we report that acute HFD feeding elicited no appreciable differences in hepatic mRNA expression of IL-1␤, TLR-4, or FFAR2 in HCR or LCR rats, suggesting that 3 days of HFD did not induce a hepatic inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, G-protein coupled receptors (GPR) such as GPR43 and GPR120 with high binding affinity to the medium-and long-chain FFAs including palmitate are upregulated in the skeletal muscle in high-fat-diet rats. 37) It is expected that palmitate, a ligand, bound GPR43 or GPR120, did not require palmitate accumulation in C2C12 myotubes, and modulated cell-signal transduction, inhibiting the insulin-stimulated phosphorylation of Src at Tyr416 through an ill-defined mechanism and downregulating the Src-mediated phosphorylation of Akt. This calls for further study.…”
Section: Discussionmentioning
confidence: 99%
“…C2C12 myoblasts were purchased from the American Type Culture Collection (Manassas, VA). The cells were cultured in DMEM supplemented with 10% (vol/vol) FCS and antibiotics (penicillin 100 U/mL, streptomycin 100 mg/mL) for growth at 37 C under a humidified atmosphere containing 5% CO 2 . To induce differentiation of the myotubes, C2C12 myoblasts were cultured in DMEM containing 2% horse serum when the cells reached approximately 90% confluence.…”
mentioning
confidence: 99%
“…Immunoreactivity for GPR120 was found to be more abundant in the mouse large intestine, lung, and adipose tissues (26). High fat diet up-regulated GPR120 gene expression in skeletal muscles (27). Although many studies suggested benign effects of DHA on human health, there is not much molecular information of the role of DHA in skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%